AUV Controller Design And Analysis Using Full-State Feedback. - Radzak, M Y; Arshad, M R (2005)
This paper presents the design and development of a system controller for our USM Autonomous Underwater Vehicle (USM-AUV). The state space design approach was used because this design approach is most suitable for nonlinear system and multi-input multi-output (MIMO) system set-up.